Voxel-based fabrication through material property mapping: A design method for bitmap printing. (March 2015) - Doubrovski, E.L.; Tsai, E.Y.; Dikovsky, D.; Geraedts, J.M.P.; Herr, H.; Oxman, N.
Abstract: We present a bitmap printing method and digital workflow using multi-material high resolution Additive Manufacturing (AM). Material composition is defined based on voxel resolution and used to fabricate a design object with locally varying material stiffness, aiming to satisfy the design objective. In this workflow voxel resolution is set by the printer's native resolution, eliminating the need for slicing and path planning. Controlling geometry and material property variation at the resolution of the printer provides significantly greater control over structure–property–function relationships. To demonstrate the utility of the bitmap printing approach we apply it to the design of a customized prosthetic socket. Pressure-sensing elements are concurrently fabricated with the socket, providing possibilities for evaluation of the socket's fit. The level of control demonstrated in this study cannot be achieved using traditional CAD tools and volume-based AM workflows, implying that new CAD workflows must be developed in order to enable designers to harvest the capabilities of AM. Highlights: Bitmap printing workflow enables digital fabrication in printer's native resolution. Voxel-based design and representation of objects for multi-material printing. Using 3D printed light guides, deformation of materials can be sensed.